Phage-antibiotic synergy against daptomycin-nonsusceptible MRSA in an ex vivo simulated endocardial pharmacokinetic/pharmacodynamic model - Kunz Coyne, Ashlan J; Bleick, Callan; Stamper, Kyle; Kebriaei, Razieh; Bayer, Arnold S; Lehman, Susan M; Rybak, Michael J (Antimicrobial agents and chemotherapy, 2024)
Phage-antibiotic combinations (PAC) offer a potential solution for treating refractory daptomycin-nonsusceptible (DNS) methicillin-resistant (MRSA) infections. We examined PAC activity against two well-characterized DNS MRSA strains (C4 and C37) and . PACs comprising daptomycin (DAP) ± ceftaroline (CPT) and a two-phage cocktail (Intesti13 + Sb-1) were evaluated for phage-antibiotic synergy (PAS) against high MRSA inoculum (10 CFU/mL) using (i) modified checkerboards (CB), (ii) 24-h time-kill assays (TKA), and (iii) 168-h simulated endocardial vegetation (SEV) models. PAS was defined as a fractional inhibitory concentration ≤0.5 in CB minimum inhibitory concentration (MIC) or a ≥2 log CFU/mL reduction compared to the next best regimen in time-kill assays and SEV models. Significant differences between regimens were assessed by analysis of variance with Tukey's post hoc modification (α = 0.05). CB assays revealed PAS with Intesti13 + Sb-1 + DAP ± CPT. In 24-h time-kill assays against C4, Intesti13 + Sb-1 + DAP ± CPT demonstrated synergistic activity (-Δ7.21 and -Δ7.39 log CFU/mL, respectively) ( < 0.05 each). Against C37, Intesti13 + Sb-1 + CPT ± DAP was equally effective (-Δ7.14 log CFU/mL each) and not significantly different from DAP + Intesti13 + Sb-1 (-Δ6.65 log CFU/mL). In 168-h SEV models against C4 and C37, DAP ± CPT + the phage cocktail exerted synergistic activities, significantly reducing bio-burdens to the detection limit [2 log CFU/g (-Δ7.07 and -Δ7.11 log CFU/g, respectively)] ( < 0.001). At 168 h, both models maintained stable MICs, and no treatment-emergent phage resistance occurred with DAP or DAP + CPT regimens. The two-phage cocktail demonstrated synergistic activity against two DNS MRSA isolates in combination with DAP + CPT and . Further PAC investigations are needed.